THU0200 DRUG UTILISATION IN PEOPLE WITH EARLY RHEUMATOID ARTHRITIS IN THE UNITED KINGDOM. (June 2019) - Wood, Sarah; Hyrich, Kimme; Verstappen, Suzanne; Steinke, Douglas
Abstract : Background: Despite a growing body of evidence in the pharmacological management of people with early rheumatoid arthritis (RA), there is still uncertainty concerning the most effective treatment regimen. Until 2018, guidance for England and Wales stated that everyone with early RA should receive combination therapy with 2 or more conventional synthetic disease modifying anti-rheumatic drugs (csDMARDs) in parallel. However, from epidemiological studies and anecdotal information, we know that this has not been the case in practice. Objectives: (i) To determine the proportion of patients with new onset RA who start methotrexate (MTX) either alone or in combination with another csDMARD (ii) to describe which combinations are currently being prescribed and (iii) to describe the characteristics associated with the choice of initial RA treatment strategy Methods: Consecutive patients with RA participating in the Rheumatoid Arthritis Medication Study (RAMS), a large UK study recruiting patients starting MTX for the first time, were eligible. Data on demographics, disease activity, comorbidity and all RA treatments are captured at baseline, 6 and 12 months following start of MTX. Analysis was limited to patients starting MTX within the first 2 years of symptom onset as part of their first treatment regimen for RA. Prevalent users of alternative csDMARDs, defined as use > 6 weeks prior to MTX start, were excluded. Participants were categorised as either starting MTX monotherapy or MTX in combination with another csDMARD (defined as started +/- 6 weeks of MTX start date). Baseline characteristics were compared between monotherapy and combination therapy groups using descriptive statistics. Results: 1, 374 patients with a mean (SD) age of 58 (14) years were included in this study; 64% were female. At baseline, 996 (76%) started MTX monotherapy and 316 (24%) started MTX/csDMARD combination therapy (84% with hydroxychloroquine and 16% with sulphasalazine). Patients starting combination therapy were younger (p<0.005), with higher DAS28 scores (p<0.005), higher HAQ scores (p<0.05), lower MTX starting doses (p<0.005), and shorter symptom duration (p<0.05) compared with the monotherapy group. Conclusion: These data show that despite national guidelines recommending combination csDMARD therapy in all patients diagnosed with RA, over three quarters of patients still started MTX monotherapy. People who were prescribed combination therapy had more severe disease suggesting that prescribers do consider prognosis in their treatment decisions. A majority of patients starting combination therapy did so with hydroxychloroquine, despite a lack of evidence for the benefits of this particular combination in clinical practice. Values are frequency (%) or median (IQR) Abbreviations: HAQ, health assessment questionnaire; DAS, disease activity score; MTX, methotrexate Disclosure of Interests: Sarah Wood Grant/research support from: Pfizer stipend received for MPhil in epidemiology in 2013, Employee of: Employed by GSK in 2012 as a pre-registration pharmacist, Kimme Hyrich Grant/research support from: Grants to institution: BMS, Pfizer, UCB, Suzanne Verstappen: None declared, Douglas Steinke: None declared